Pengaruh Penggunaan Media Pembelajaran Lettrum Box Untuk Meningkatkan Kemampuan Numerasi Anak Usia Dini - Tita, Tita Bonita Irianfi; Intan Prastihastari Wijaya; Dwiyanti, Linda (Jurnal Kajian Anak (J-Sanak), 2025)
This research is motivated by findings at the Mojoroto State Kindergarten, where the basic numeracy skills of early childhood children are still low. Many children are unable to distinguish numbers and count correctly, and there is a lack of use of educational learning media. To address this issue, the researcher created a learning media called "Lettrum box" using a quasi-experimental method and a quantitative approach. The study involved 24 children, divided into a control class (A2) and an experimental class (A1). Each class participated in five learning sessions. The research instrument was a numeracy post-test with five questions per session. The post-test results showed a significant difference between the two groups. The average score of the control group was 8.00, while the experimental group reached 16.31. This research aims to improve the basic numeracy skills of early childhood children. Thus, the learning media "Lettrum box" has been proven effective in enhancing the numeracy skills of early childhood children in early childhood education institutions.